EVALUACION DE PELIGROS Y RIESGOS OCUPACIONALES EN EL MERCADO MAYORISTA PESQUERO DE BUENOS AIRES, TRUJILLO - LA LIBERTAD, PERU - Ruiz Bardales, Fiorela Alexandra (2018)
The objective of the research was to determine the hazards and occupational risks in the Fishing Wholesale Market of Buenos Aires. The sample was constituted by the workers of the Wholesale Market in charge of the manipulation and sale of the hydrobiological resources. The existing jobs were identified, in order to evaluate the conditions and/or work situations and to be able to identify the hazards to which they are exposed. To evaluate the risk, the quantitative method proposed by MINTRA was applied; hazards and risk were recorded in an IPER matrix. The JSI and REBA ergonomic methods were used to determine the level of ergonomic risk. It was found that the danger of ergonomic type is the most frequent, the risks presented 5% to occupational health and 4% to safety. The JSI method showed that the task of loading presented a very high level of risk, and the REBA method presented very high-risk levels in almost all present tasks. It can be concluded that in the wholesale fishing market I present very high-risk levels in the accomplishment of the tasks, being necessary the application of control measures to avoid labor accidents.KEY WORDS: Occupational hazards, Occupational risks, IPER, JSI, REBA